Исламские финансы. Репортаж с XX Апрельской международной научной конференции по проблемам развития экономики и общества, 9–12 апреля 2019 г., Москва, Россия - Dzhangiryan Shushanik (Journal of Economic Sociology, 2019)
Traditionally, the XXth April International Academic Conference on Economic and Social Development has been organized at the Higher School of Economics. On the 11th of April 2019, Sheikh Muhammad Taqi Usmani (Darul Uloom Krachi) made an honorary report about Islamic finance in the 21st century. The Sheikh is one of the leading experts of Islamic law, economics, and finance, and he ranks 6th in the “The World’s 500 Most Influential Muslims 2019” [Schleifer 2019]. He currently leads the International Shariah Council for the Accounting and Auditing Organization for Islamic Financial Institutions. As a part of his speech, he touched on some aspects related to Islamic finance and its distinctive features. The report also provided an introduction to the functioning of Islamic finance. The Sheikh explained the meaning of the concept as well as its basis, referring to the principles of the Koran. Then he highlighted the main aspect related to Islamic finance—the prohibition of collecting interest. This rule applies not only to Islamic organizations and banks, but also to self-employed entrepreneurs and individuals. Among other things, the speaker touched on the role of Islamic finance during the crisis, demonstrating the positive aspects of the system for both Muslims and people of other faiths.